"And then I see the disinfectant where it knocks it out in a minute": Donald Trump as patient zero and superspreader of Covid-19 cartoon logic. (2nd September 2022) - Polak, Sara; Zwetsloot, Anne
ABSTRACT: In Donald Trump's response to the Covid-19 pandemic, and particularly around his own bout with the disease, the intersection of "traditional" themes and tropes – i.e. the representation and narration of communicable disease, presidential image-making, and the visual language of play and politics – come together in novel manners. We will argue that Trump's employment of cartoon logic relies on his grotesquely exaggerated treatment of pre-existing norms, which generates speculation, innuendo, and in reaction an often cartoonesque meme production. Through an investigation of three case studies – the rumour that Trump would return into public view revealing a Superman shirt, Trump's slapdash suggestion that imbibing disinfectant might cure Covid-19, and his treatment of face masks – we arrive at the conclusion that cartoon logic can generate online political constituencies. The memes' visual rhetoric moves gradually from cartoonesque, narrative, and directly related to Trump's body and person (as in the case of the Superman rumour), to more photographic and more directed at broader consumer behaviour, though still decidedly absurd (as in the case of the disinfectant claim), to acutely and directly politicising constituents' everyday behaviour (as in the case of Trump's masking and unmasking claims).